The perception of dental students and educators about e-learning during COVID-19 pandemic - Fouda, Shaimaa M; Madi, Marwa; Ellakany, Passent; Aly, Nourhan M; Bahgat, Hala A; Elembaby, Abeer E; Virtanen, Jorma I; AlHumaid, Jehan (United Kingdom, 2025)
Background: The COVID-19 pandemic necessitated an abrupt shift to e-learning in higher education institutions worldwide to ensure educational continuity during lockdowns. The aim of this study was to evaluate dental students' and educators' perceptions of e-learning during the COVID-19 lockdown and their attitudes toward implementing blended learning in post-pandemic dental education.
Methods: A cross-sectional survey regarding e-teaching during the COVID-19 pandemic was conducted at the College of Dentistry. Satisfaction and attitude towards technology-based learning (TBL) were assessed. Two binary logistic regression models were performed to assess the association of factors (age, gender, Grade Point Average, IT skills and experience in TBL) with educators and students' overall satisfaction and attitude towards TBL. The teaching staff attitude towards TBL was also assessed. Adjusted odds ratios (AOR), and 95% confidence intervals (CI) were calculated. Significance was set at p value < 0.05.
Results and conclusions: The study included 431 students and 74 teaching staff (response rate = 92.1% and 75.6%). Most students and teaching staff rated their computer skills as intermediate (≈ 67%), and most students (77.5%) reported a fair experience in TBL. Most students were satisfied and showed a positive attitude towards the TBL experience. Male and older students showed significantly higher overall satisfaction and attitude than female and younger students. Nevertheless, most teaching staff easily adapted to the shift from traditional to TBL (74.3%), and preferred blended learning after the pandemic (73%). However, only a few of them prefer TBL in all teaching activities.